Corruption and Its Implications for Development and Good Governance: A Perspective from Post-Colonial Africa - Mlambo, Daniel N.; Mubecua, Mandla A.; Mpanza, Siphesihle Edmund; Mlambo, Victor H. (Journal of Economics and Behavioral Studies, 2019)
Abstract: One of the many impediments to a specific region, country and/or continents political, social and economic growth prospects is corruption, the aim of this paper is to unearth the drivers and consequences of corruption in post-colonial Africa. Corruption is a global phenomenon; however when observing global corruption statistics and/or trends, it seems to be more prominent in underdeveloped continents such as Africa. Corruption in Africa is purely driven by low levels of economic growth, bad governance structures weak constitutions political instability, high levels of poverty coupled with high and ever-increasing levels of unemployment. We argue that post the colonial era, there has been a rise of corruption activities within the continent where individuals including some African heads of states have looted the continent of its resources meant for the general populace. In this sense, corruption takes resources meant for the poor, limits foreign direct investments (FDI) and has severe effects on a continent that is already the least developed in the world.